The algorithm of adaptation by using graded meshes generator - Kucwaj, Jan (Computer Assisted Methods in Engineering and Science, 2023)
An algorithm of remeshing based on graded meshes generator is presented. The algorithm starts with an initial grid, which is iteratively improved taking into account error estimate. Mesh density functions are used to generate grid over domain on which boundary value problem is solved. It is observed, that successive meshes are convergent and especially they become denser near singularities. For unstructured grid generation the advancing front technique combined with Delaunay triangulation is used. The boundary of 2-D domain may be represented by B-spline curves. It may be multiconnected.